Research on corporate diversification: A synthesis - Ramanujam, Vasudevan; Varadarajan, P. Rajan (Strategic Management Journal, 1989)
Abstract Diversification has emerged as a central topic of research in strategic management. Although this topic has been widely and intensively studied by scholars from other areas such as industrial organization economics, financial economics, organization theory, and marketing, a synthesis of these diverse streams of research is lacking. This paper attempts such a synthesis with a view to fostering further strategic management research in this area by taking a multi‐disciplinary perspective on diversification. A wide‐ranging search of the literature led to the development of an overarching research framework that facilitates the classification of a vast body of literature. Proceeding from the framework, a critique of the literature is performed with a particular emphasis on studies by strategic management researchers. Five key conceptual and methodological problems are identified and discussed. Suggestions are offered for future research on diversification.